ASSESSMENT OF HUMAN RESOURCE MANAGEMENT IN THE ADVANCEMENT OF ECOTOURISM AT THE GUNUNG TUNAK NATURE TOURISM PARK DESTINATION - Rumba, Rumba; Rahayu M. (Bajang Institute, 2025)
Human Resource Management (HRM) assumes a critical function in fostering the sustainability and advancement of natural tourism destinations, such as the Gunung Tunak Nature Tourism Park (TWA). This study seeks to assess the efficacy of human resource management, specifically via the training of tour guides and ongoing education, in enhancing the quality of tourism services and environmental conservation. This study highlights the role of human resource management in fostering sustainable ecotourism at TWA Gunung Tunak as a conservation tourism site. The study employs a qualitative methodology, including interviews and field observations to examine the execution of training programs and their effects on ecotourism operations. The research findings suggest that while knowledge concerning ecological and cultural heritage exists, there is a necessity to augment training quality, offer competency certification, and improve access to digital material. Enhancing human resource capability in advanced education, multi-stakeholder engagement, and supportive policies is essential for attaining optimal and sustianable ecotourism management in this region